A new Hoplia Illiger, 1803 from Calabria, southern Italy (Coleoptera: Scarabaeidae: Melolonthinae: Hopliini) - Patacchiola, Daniel; Fabbriciani, Fabrizio; Boschin, Pier Luigi; Manti, Francesco; Castiglione, Elvira; Bonsignore, Carmelo Peter; Grimaldi, Enrica Giuliano; Biscaccianti, Alessandro Bruno (Zootaxa, 2022)
Hoplia asprumuntiana Patacchiola, Fabbriciani, Boschin & Biscaccianti, new species from Aspromonte National Park (Calabria, southern Italy) is described and illustrated. The new species is compared with the two apparently most closely related species, namely H. maremmana Leo, Liberto, Rattu & Sechi, 2010 and H. meridiana Uliana, Liberto & Leo, 2017. The differences between H. asprumuntiana new species and the other Hoplia Illiger, 1803 occurring in the southern Apennine are also discussed, chiefly regarding H. paganettii Müller, 1907 described from Aspromonte. Some remarks on ecology and phenology of adults are also reported.